Doctoral dissertation: A geographic model development for the analysis of solar potential in urban environments from LIDAR data - Javier Domínguez Bravo (Boletín de la Asociación de Geógrafos Españoles)
Martín Ávila, Ana María. A geographic model development for the analysis of solar potential in urban environments from LIDAR data. Complutense University of Madrid (Spain), April 2023. Director: Dr. Javier Domínguez Bravo.